Digital Light Processing of 19F MRI-Traceable Gelatin-Based Biomaterial Inks towards Bone Tissue Regeneration - Szabó, Anna; Kolouchova, Kristyna; Parmentier, Laurens; Herynek, Vit; Groborz, Ondrej; Van Vlierberghe, Sandra (Materials (Basel, Switzerland), 2024)
Gelatin-based photo-crosslinkable hydrogels are promising scaffold materials to serve regenerative medicine. They are widely applicable in additive manufacturing, which allows for the production of various scaffold microarchitectures in line with the anatomical requirements of the organ to be replaced or tissue defect to be treated. Upon their in vivo utilization, the main bottleneck is to monitor cell colonization along with their degradation (rate). In order to enable non-invasive visualization, labeling with MRI-active components like N-(2,2-difluoroethyl)acrylamide (DFEA) provides a promising approach. Herein, we report on the development of a gelatin-methacryloyl-aminoethyl-methacrylate-based biomaterial ink in combination with DFEA, applicable in digital light processing-based additive manufacturing towards bone tissue regeneration. The fabricated hydrogel constructs show excellent shape fidelity in line with the printing resolution, as DFEA acts as a small molecular crosslinker in the system. The constructs exhibit high stiffness (E = 36.9 ± 4.1 kPa, evaluated via oscillatory rheology), suitable to serve bone regeneration and excellent MRI visualization capacity. Moreover, in combination with adipose tissue-derived stem cells (ASCs), the 3D-printed constructs show biocompatibility, and upon 4 weeks of culture, the ASCs express the osteogenic differentiation marker Ca2+.
Keywords: tissue engineering; photo-crosslinkable gelatin; poly[N-(2,2-difluorethylacrylamide)]; fluorine-19 magnetic resonance imaging; digital light processing